Condiciones de la innovación pecuaria y producción de lácteos en comunidades altoandinas - Rosas Morales, Diana (2020)
Summary The study explores the conditions of the changes that have occurred in the livestock activity of two communities in the southern Andes of Peru, based on innovation in the processes of cattle production for obtaining milk. A mixed methodology was used that involved the development of interviews and surveys with the families of producers in the district of Ocongate. The results show an increase in the number of heads of cattle and cattle breeders, improvements in milk production, an increase in family income, and other changes in the family life of producers. In addition, it is argued that the involvement of both governmental and private institutions contributed to livestock innovation.